Factors Related to Mortality in Patients with Fournier’s Gangrene or Necrotising Fasciitis; a 10-year Cross-Sectional Study - Ansari Djafari, Anahita; Rahavian, Amirhossein; Javanmard, Babak; Montazeri, Saeed; Shahabi, Vahid; Hojati, Seyyed Ali; Ghiasy, Saleh; Hamidi, Ramin; khoshnevis, jalallodin (Archives of Academic Emergency Medicine, 2021)
Introduction: Fournier’s gangrene (FG) is a life-threatening disease, even with early diagnosis and administration of vigorous treatment, its mortality rate is high. This study aimed to evaluate the factors relate to mortality in patients with FG or necrotising fasciitis managed in a referral center. Methods: This retrospective cross-sectional study was conducted on patients managed in a tertiary referral center, Tehran, Iran, from March 2009 to March 2019, with diagnosis of FG or necrotising fasciitis. The correlation between different demographic and clinical parameters with mortality was analysed and reported. Results: 73 cases with the mean age of 59.1 ± 15.8 (range: 25 – 88) years were studied (87.7% male). 21 (28.8%) patients died. Escherichia coli (26 cases, 35.6%) was the most frequent microorganism in cultures. Non-survived cases had higher mean age (p = 0.01), higher frequency of hyperlipidaemia (p = 0.02), immunosuppression (p < 0.001), longer hospital stay (p=0.02), lower blood pressure (p=0.01), and lower platelet count (p=<0.001). Based on multivariate analysis, age (p = 0.015; Odds: 0.88 (0.79-0.97)), haematocrit level (p = 0.01; Odds: 1.27 (1.04-1.55)), platelet count (p = 0.03; Odds: 10.11 (1.14-89.35)), and immunosuppression (p = 0.01; Odds: 0.01 (0.0-0.54)) were independent related factors of mortality. Conclusions: The rate of mortality due to FG and necrotizing fasciitis was 28.8%. Based on multivariate analysis, the independent related factors of mortality were older age, lower haematocrit level and platelet count, and presence of immunosuppression.